A lithium ion battery with a porous electrode structure

By setting an electrolyte flow channel through the electrode film in the electrode of the lithium-ion battery, the problem of low impregnation of the electrolyte is solved, and efficient liquid injection and battery performance are achieved.

CN117457966BActive Publication Date: 2025-03-21广东比沃新能源股份有限公司
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202311298232.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-03-21
Estimated Expiration
2043-10-09

AI Technical Summary

Technical Problem

During the injection process of existing lithium-ion batteries, due to the decrease in electrode porosity, the electrolyte is wettable, and the injection process is cumbersome, time-consuming and inefficient. Especially in the manufacturing of large cylindrical batteries, the injection aging problem has become a technical bottleneck restricting efficient manufacturing.

Method used

A lithium-ion battery with a pore structure of electrodes is designed. By setting an electrolyte flow channel through the electrode inside the electrode film, a flow channel and a shaft are prepared by laser etching or mechanical needle puncture to form a channel matrix to improve the wettability and fluidity of the electrolyte.

Benefits of technology

The electrolyte is efficiently soaked in the battery cell, simplified the liquid injection process, and improved the liquid injection efficiency and the energy density, cycle stability and power characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117457966B_ABST
    Figure CN117457966B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium-ion battery with a porous electrode structure, and relates to the technical field of lithium batteries. The lithium-ion battery of the present invention comprises a positive electrode sheet, a negative electrode sheet and a separator; the surface of the positive electrode sheet and / or the negative electrode sheet is provided with a coating film layer, and the coating film layer is provided with a channel for storing and circulating electrolyte; the positive electrode, the separator and the negative electrode are stacked, wound and assembled to form a battery core; the battery core is then infiltrated with electrolyte; finally, the lithium-ion battery is obtained after sealing and formation. The present invention solves the most critical problem of the difficulty of electrolyte infiltrating the inside of the battery core by providing an electrolyte circulation channel that runs through the inside of the electrode film in the electrode. Compared with the method of achieving electrolyte infiltration by batch injection, multiple vacuuming and gas replenishment, the method adopted by the present invention is efficient, low-cost, simple and easy to implement, and suitable for rapid promotion of production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a lithium ion battery with a pore structure as an electrode. Background Art

[0002] Lithium-ion batteries have been widely used in portable electronic products, electric vehicles, power tools and energy storage due to their advantages such as high energy density, high power and long cycle life. In recent years, with the continuous improvement of battery energy density, the compaction density of battery electrodes has become larger and larger, and the overall thickness of the battery core has become thicker and thicker. As a result, according to the current traditional structure of battery pole piece design, the porosity of the battery pole piece is greatly reduced, and the wettability of the electrolyte to the pole piece is seriously reduced, which ultimately leads to the complicated, time-consuming and inefficient injection process. Especially in recent years, for large cylindrical batteries represented by models such as 4680 and 46135, the injection time aging problem has become one of the technical bottlenecks restricting the efficient manufacturing of such batteries. At the same time, as the main place for electrolyte storage, the structure and number of pores in the electrode also directly affect the power performance and cycle life performance of lithium batteries. Therefore, designing pole pieces and lithium-ion batteries with good electrode pore structure is one of the core technologies of lithium-ion batteries and their products.

[0003] At present, invention patents CN112599940A, CN105529429A, CN113921917A, CN105977443A and CN112821017A respectively disclose the use of different stages to improve the wettability of the electrolyte to the electrode by adjusting the pressure and time combination of multiple vacuum pumping and nitrogen replenishment. This type of method can improve the wetting effect of the electrolyte on the electrode to a certain extent, but the multiple vacuum pumping and nitrogen replenishment processes not only cause waste of energy and drying gas, but also have no significant effect on shortening the injection time.

[0004] Invention patents CN116231248A, CN116093441A and CN114865252A also eliminate bubbles by ultrasound, vibration and the like during the liquid injection process to accelerate the electrolyte penetration rate. This type of method can solve the problem of difficulty in liquid injection caused by gas resistance inside the electrode to a certain extent, and can make up for the above-mentioned deficiency of needing to eliminate this influence through multiple vacuum exhausts. However, the vibration process has an uncertain impact on the internal assembly structure of the battery cell and the bonding effect of the electrode material on the current collector.

[0005] Invention patent CN1112542641A discloses that the contact density between the positive and negative ears is reduced by adding laser cutting of the pole pieces to accelerate the filling efficiency of the cylindrical battery. Invention patent CN115602923A discloses that a flow guide cavity is formed at both ends of the core body to improve the patency of the exhaust to improve the penetration of the electrolyte. Although both methods provide better conditions for the electrolyte to contact the top of the pole piece, the lack of an effective channel for the electrolyte to reach the central area of ​​the battery cell is the main bottleneck for the long filling time of the cylindrical battery cell. The above methods do not provide an effective solution to this key core problem. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a lithium ion battery with a porous electrode structure. The lithium ion battery of the present invention has excellent power type and cycle performance.

[0007] The present invention is achieved by adopting the following technical solutions:

[0008] A lithium-ion battery with a porous electrode structure, comprising a positive electrode sheet, a negative electrode sheet and a separator; the surface of the positive electrode sheet and / or the negative electrode sheet is provided with a coating film layer, and the coating film layer is provided with channels for storing and circulating electrolyte; the positive electrode, the separator and the negative electrode are stacked, wound and assembled to form a battery core; and the electrolyte is then infiltrated into the battery core. After sealing and formation, a lithium-ion battery is obtained.

[0009] Preferably, the electrode sheet is provided with a channel which forms an acute angle with the plane where the battery electrode sheet is located and the width direction of the electrode sheet, and which leads from the electrode surface to the electrode coating layer membrane, which is a flow channel; or / and, the electrode sheet is provided with a channel which is perpendicular to the plane where the electrode is located and connects the electrode surface and the flow channel, which is a well channel;

[0010] The pole piece and the flow channel start from the edge of the pole piece in the height direction, that is, from the proximal end surface of the subsequent battery cell winding core.

[0011] Preferably, the battery electrode flow channel and / or the well channel can be prepared by one or more methods including laser etching and mechanical acupuncture.

[0012] Preferably, the flow channel forms an acute angle with the plane where the electrode surface is located, and forms an acute angle with the running direction or length direction of the electrode sheet, and the depth of the flow channel can be adjusted according to the coating thickness of the electrode;

[0013] The depth is determined by the electrode coating thickness and the depth of the connection position with the flow channel, and can be adjusted.

[0014] Preferably, the well is a hole perpendicular to the electrode surface, leading from the electrode surface to the inside of the electrode coating layer and connected to the flow channel. The depth of the well is determined by the thickness of the electrode coating and the depth of the connection with the flow channel, and can be adjusted.

[0015] The relative distance between the flow channel and the well entrance can be adjusted according to the pore density requirements of the pole piece pore making.

[0016] Preferably, the lithium-ion battery is a large cylindrical lithium-ion battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The present invention solves the most critical problem of electrolyte infiltration into the battery cell by providing an electrolyte flow channel that penetrates the interior of the electrode membrane. Compared with the conventional method of achieving electrolyte infiltration by batch injection, multiple vacuum pumping and gas replenishment, the method adopted by the present invention is highly efficient, low-cost, simple and easy to implement, and suitable for rapid promotion and production application.

[0019] (2) The pores provided inside the electrode of the present invention not only provide channels for the flow of electrolyte, but also provide more liquid storage places, so that the electrode has a stronger liquid retention capacity. Therefore, the lithium-ion battery of the present invention has a high energy density while ensuring good cycle stability and power characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the battery pole piece structure and electrolyte path process of the present invention;

[0021] Figure 2 This is a diagram showing the implementation effect of the lithium-ion battery described in Example 1 of the present invention;

[0022] Figure 3 This is a schematic diagram of the pore matrix of the lithium-ion battery electrode described in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with specific embodiments.

[0024] Example 1

[0025] Using lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O 2) Positive electrode plate, the total length of the plate coating is 4970mm, the width is 87mm, and the single-side thickness of the coating film is 54.5μm. Set up laser / laser group 1 and laser / laser group 2, and use the laser / laser group to emit pulsed laser to prepare channels. Through laser / laser group 1, from 1mm away from the edge in the height direction of the positive electrode plate, perpendicular to the length direction of the electrode plate, at a 45° angle to the plane where the electrode is located, a flow channel hole is made in the coating film layer, with a pore diameter of 3μm and a hole depth of 74μm, which is the flow channel L00. Through laser / laser group 2, with the surface entrance of the above-mentioned flow channel hole as the positioning standard, along the direction of the flow channel hole, 52.5μm away from the entrance of the flow channel hole, laser etching is performed to obtain a well perpendicular to the plane of the electrode plate and connected to the flow channel. The depth of the well is between 52.5 and 54.0μm, which is the well J00. Each of the flow channels obtained as described above is connected to a well, which is a group of channels, LJ00. In the width direction of the electrode, along the extension direction of the flow channel, the flow channel and its entrance of the second group of channels are set on the electrode surface 3mm away from the entrance of the first group of wells, which is L01. Similar to LJ00, a second well in the width direction is made, which is J01. L01 and J01 form the second group of channels LJ01. And so on until the width direction is full. In the length direction of the electrode, at the same position as the entrance of the first group of flow channels from the edge, 20mm away from the entrance of the first group of flow channels in the length direction, the second group of flow channels, L10, and the well J10 in a group with it are made, forming the second group of channels LJ10 in the length direction. Finally, a pole piece channel matrix from LJ00 to LJnn is formed, as shown in the attached figure. Figure 3 After the obtained electrode sheet is stacked with the matching separator and negative electrode, it is wound, put into the shell, filled with liquid, vacuumed, sealed and formed to obtain a 4695 large cylindrical battery.

[0026] Example 2

[0027] The positive electrode sheet is made by the same pore manufacturing method as in Example 1;

[0028] A graphite negative electrode is used, the total length of the electrode is 5110mm, the width is 89mm, and the single-side thickness of the coating film is 70.5μm. The flow channel and well are set in a similar way to the positive electrode. The flow channel aperture is 3μm, the hole depth is 80.0μm, and the well depth is between 56.5 and 70.0μm. The arrangement and number of channels are set in the same way as the positive electrode. After the obtained positive electrode sheet is superimposed with the matching diaphragm and the obtained negative electrode, the 4695 large cylindrical battery is obtained by winding, shelling, liquid injection, vacuuming, sealing, and formation.

[0029] Example 3

[0030] A lithium iron phosphate (LiFePO4) positive electrode is used, the total length of the electrode coating is 5500mm, the width is 115mm, and the single-side thickness of the coating film is 72μm. Laser / laser group 1 and laser / laser group 2 are set, and the laser / laser group emits pulsed laser to prepare channels. Through laser / laser group 1, from the height direction of the positive electrode sheet 1mm away from the edge, perpendicular to the length direction of the electrode sheet, at an angle of 60° to the plane where the electrode is located, a flow channel hole is made in the coating film layer, with a pore diameter of 3.5μm and a hole depth of 55.5μm, which is the flow channel L00. Through laser / laser group 2, with the above-mentioned flow channel hole surface entrance as the positioning standard, along the flow channel channel direction, 27.7μm away from the flow channel hole entrance, laser etching is made to obtain a well perpendicular to the plane of the electrode sheet and connected to the flow channel, and the well depth is between 64 and 72μm, which is the well J00. Each of the above-mentioned channels is connected to a well, which is a group of channels, LJ00. In the width direction of the electrode, along the extension direction of the channel, the flow channel and its entrance of the second group of channels are set at 3mm from the entrance of the first group of wells on the electrode surface, which is L01. Similar to LJ00, a second well in the width direction is made, which is J01. L01 and J01 form the second group of channels, which is LJ01. And so on until the width direction is full. In the length direction of the electrode, at the same position as the entrance of the first group of flow channels from the edge, the second group of flow channels, L10, and the well J10 in a group with it are made at 20mm from the entrance of the first group of flow channels in the length direction, forming the second group of channels LJ10 in the length direction. Finally, a pole piece channel matrix from LJ00 to LJnn is formed.

[0031] A graphite negative electrode is used, with a total length of 5533mm and a width of 118mm. The thickness of the coating film on one side is 48.5μm. The channel setting method is similar to that of the positive electrode, and the flow channel and well channel are made. The flow channel aperture is 3.5μm, the hole depth is 31.2μm, and the well channel depth is between 36 and 48μm. The channel arrangement and quantity setting are the same as the positive electrode setting method.

[0032] The obtained positive electrode sheet is stacked with the matching separator and the obtained negative electrode, and then wound, shelled, liquid-filled, vacuumed, sealed and formed to obtain a 46135 large cylindrical battery.

[0033] Comparison table of program implementation effects

[0034] project Complete wetting time (min) Liquid absorption rate (g / Ah) Conventional structural scheme 23.5 2.72 Example 1 Scheme 17.2 2.84 Example 2 Scheme 7.8 3.16 Example 3 Scheme 7.7 3.81

[0035] It should be noted that the above are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and other variations are possible. All variations directly or indirectly derived from the disclosure of the present invention by those skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing a lithium-ion battery having a porous electrode structure, characterized in that: A lithium iron phosphate positive electrode plate is used, the total length of the plate coating is 5500mm, the width is 115mm, and the single-side thickness of the coating film is 72μm. A laser / laser group 1 and a laser / laser group 2 are set, and a pulsed laser is emitted by the laser / laser group to prepare a channel; through the laser / laser group 1, a flow channel hole is made in the coating film layer at an angle of 60° to the plane where the electrode is located, from 1mm away from the edge in the height direction of the positive plate, perpendicular to the length direction of the plate, and at a direction of 60° to the plane where the electrode is located. The hole diameter is 3.5μm and the hole depth is 55.5μm, which is the flow channel L00; through the laser / laser group 2, with the surface entrance of the above-mentioned flow channel hole as the positioning standard, along the direction of the flow channel hole, 27.7μm away from the entrance of the flow channel hole, laser etching is performed to obtain a well perpendicular to the plane of the plate and connected to the flow channel, and the depth of the well is between 64 ~72μm, which is the well J00; each flow channel obtained as described above is connected to a well, which is a group of channels, LJ00; in the width direction of the electrode, along the extension direction of the flow channel, on the electrode surface 3mm away from the entrance of the first group of wells, the flow channel and its entrance of the second group of channels are set, which is L01, and the second well in the width direction is similar to LJ00, which is J01. L01 and J01 form the second group of channels, which is LJ01, and so on until the width direction is full; in the length direction of the electrode, at the same position as the entrance of the first group of flow channels from the edge, the second group of flow channels, L10, and the well J10 in a group with it are built at 20mm away from the entrance of the first group of flow channels in the length direction, forming the second group of channels LJ10 in the length direction, and finally forming a pole piece channel matrix from LJ00 to LJnn; A graphite negative electrode is used, the total length of the electrode is 5533mm, the width is 118mm, the single-side thickness of the coating film is 48.5μm, and the channel setting method is similar to the positive electrode, the flow channel and the well channel are made, wherein the flow channel pore diameter is 3.5μm, the pore depth is 31.2μm, the well channel depth is between 36 and 48μm, and the channel arrangement and quantity setting are the same as the positive electrode setting method; The obtained positive electrode sheet is stacked with the matching separator and the obtained negative electrode, and then wound, shelled, liquid-filled, vacuumed, sealed and formed to obtain a 46135 large cylindrical battery.

Citation Information

Patent Citations

  • Liquid filling method for cylindrical lithium-ion battery

    CN105529429A

  • Liquid injection method of lithium-ion battery

    CN105977443A

  • Liquid injection method for solving problem of square aluminum shell battery shell recession

    CN112599940A

  • Liquid injection method of lithium ion battery

    CN112821017A

  • Electrolyte infiltration method of lithium ion battery

    CN113921917A